Reviving Hope: A Homeopathic Triumph over Pancreatic Necrosis with Ascites: Evidence-Based Case Report - Saklani, Nitin Kumar; Verma, Divya; Verma, Bhavya (Homœopathic Links, 2025)
Walled-off pancreatic necrosis (WOPN) is a severe complication of acute pancreatitis, characterized by encapsulation of necrotic debris. The management of WOPN poses significant challenges due to its potential for infection, hemorrhage, and multi-organ failure. Homeopathy, known for its gentle and noninvasive approach, offers a treatment mode that aims to support healing without aggressive interventions. This case report talks about a patient presenting with WOPN with ascites managed with homeopathy. A 2-year-old boy was brought to the pediatric clinic with a chief complaint of worsening abdominal distension. The parents reported a gradual increase in the size of the child's abdomen over the past few weeks, accompanied by persistent and severe abdominal pain. The child exhibited signs of discomfort, frequently expressing pain through crying and restlessness. In addition to abdominal distension and pain, the child presented with episodes of vomiting. Despite multiple attempts with various medications, including domperidone for controlling vomiting, there was no significant improvement in these symptoms. The parents also noted a concerning loss of appetite in the child, with a noticeable decrease in oral intake. The primary diagnosis was cystic lesion replacing pancreatic body and tail (12.2 × 12.3 × 9.1 Cubic centimeter) likely WOPN with gross ascites, confirmed by contrast-enhanced computed tomography of the abdomen done in the Department of Radiodiagnosis, PGIMER, Chandīgarh. The patient underwent homeopathic treatment at the Regional Research Institute for Homoeopathy in Shimla. Following the intervention, the patient achieved full recovery from the signs and symptoms of WOPN. Radiological investigations, specifically a whole abdomen ultrasound, revealed the complete dissolution of the cystic lesion along with the resolution of gross ascites. The success was evidenced by the resolution of both clinical symptoms and radiological findings, as observed in the complete dissolution of the cystic lesion and the absence of gross ascites. This suggests a potential positive role for homeopathy in the management in such life-threatening and intractable cases of WOPN, encouraging further exploration and research in this area.
Keywords: homeopathy; pancreatic necrosis; ascites; alternative medicine; case report